FREQUENCY OF COMPLETE HEART BLOCK IN PATIENTS PRESENTING WITH ACUTE ANTERIOR WALL MYOCARDIAL INFARCTION - Muhammad Ali Khan; Kinza Sammar; Raisa Naz; Shazia Tauqeer; Maria Shafiq; Shabana Naz (Journal of Ayub Medical College Abbottabad, 2024)
Background: Complete heart block (CHB) is a relatively common complication in post-acute myocardial infarction (AMI) patients. Data on the incidence and consequences of CHB in patients with ST-segment elevation myocardial infarction (STEMI) are limited. Besides serving as an indicator of widespread myocardial injury, the development of CHB in STEMI is also associated with a higher risk of sudden cardiac death. Although there has been an observed increase in the incidence of CHB complicating STEMI over the past few decades, attributed to improved reporting and timely diagnosis, the absolute or true incidence of CHB in STEMI patients receiving current management is underestimated. The present study aimed to determine the frequency of complete heart block in patients presenting with acute anterior wall myocardial infarction (AWMI). Methods: This was a descriptive study conducted in the Cardiology Department of Ayub Teaching Hospital, Abbottabad, from February to July 2020. All patients (N=244) presenting with acute Anterior Wall ST-segment elevation Myocardial Infarction were included, with ages ranging from 20 to 80 years and both genders (males and females) considered. Results: The mean age of the patients was 55.98±12.224, ranging from 20 to 80 years, out of a total of 244 patients. In terms of gender distribution, there were 160 (65.6%) males and 84 (34.4%) females. Regarding the frequency of smokers, 63 (25.8%) were smokers, and 181 (74.2%) were non-smokers. The frequency of complete heart block was 8 (3.3%), while 236 (96.7%) did not have acute anterior wall myocardial infarction-associated heart block. Conclusion: Patients admitted with inferior wall MI and right ventricular (RV) infarction were at an increased risk of mortality. The high incidence of heart block in AWMI suggests that underlying infarction and tissue damage may be extensive, leading to increased mortality secondary to complete cardiac failure.